2023
DOI: 10.3389/fimmu.2023.1142319
|View full text |Cite
|
Sign up to set email alerts
|

The necroptosis related gene LGALS3 can be used as a biomarker for the adverse progression from chronic HBV infection to HCC

Abstract: The number of patients with hepatocellular carcinoma (HCC) caused by hepatitis B virus (HBV) infection remains large, despite the remarkable effectiveness of antiviral drugs and vaccines for HBV in preventing and treating HBV infection. Necroptosis is closely related to the occurrence of inflammation, clearance of viral infection, and tumor progression. Presently, little is known about the changes in necroptosis-related genes in the progression from chronic HBV infection (CHI) to HBV-related hepatic fibrosis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…LAPTM4B as a risk factor in a scoring system which has been shown to induce autophagy and promote tumour growth in HCC [ 38 ]. LGALS3 has been shown to be used as a potential biomarker for the malignant progression of HBV infection to HCC and is thought to be associated with necroptosis in HCC [ 39 ]. Notably, the role of RPS8 in HCC has not been elucidated, and given the prognostic predictive value of TRSSys for HCC, its regulatory mechanism in HCC warrants further subsequent exploration.…”
Section: Discussionmentioning
confidence: 99%
“…LAPTM4B as a risk factor in a scoring system which has been shown to induce autophagy and promote tumour growth in HCC [ 38 ]. LGALS3 has been shown to be used as a potential biomarker for the malignant progression of HBV infection to HCC and is thought to be associated with necroptosis in HCC [ 39 ]. Notably, the role of RPS8 in HCC has not been elucidated, and given the prognostic predictive value of TRSSys for HCC, its regulatory mechanism in HCC warrants further subsequent exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Gal-3 has been closely associated with a poor prognosis of primary HCC, by promoting tumor cell growth, migration and invasion, stimulating angiogenesis and enhancing the tumorigenesis and metastasis of HCC cells [24,42,43]. After persistent HBV infection, Gal-3 was demonstrated to play a key role in adverse disease progression and to be a potential therapeutic target [44]. In this study, LGALS3 expression was negatively correlated with the overall survival of HCC patients (Figure 8C), which was consistent with the levels of ITGB1 and IL-10 (Figure S3).…”
Section: Discussionmentioning
confidence: 99%
“…Dong et al established a prognosis score for patients with HBV-HCC based on necroptosis related genes, effectively stratified the patients’ prognosis, and found that LGALS3 could be used as a biomarker for the adverse progression of chronic HBV infection. 46 Therefore, it is reasonable and promising to build predictive models or discover biomarkers based on database big data and verify them. Recently, Zhong et al established a risk score model from the perspective of anoikis, which was externally verified by ICGC cohort but not internally verified in TCGA cohort.…”
Section: Discussionmentioning
confidence: 99%